2019
DOI: 10.1152/ajpregu.00336.2018
|View full text |Cite
|
Sign up to set email alerts
|

Two nights of recovery sleep restores the dynamic lipemic response, but not the reduction of insulin sensitivity, induced by five nights of sleep restriction

Abstract: Chronic inadequate sleep is associated with increased risk of cardiometabolic diseases. The mechanisms involved are poorly understood but involve changes in insulin sensitivity, including within adipose tissue. The aim of this study was to assess the effects of sleep restriction on nonesterified fatty acid (NEFA) suppression profiles in response to an intravenous glucose tolerance test (IVGTT) and to assess whether 2 nights of recovery sleep (a “weekend”) is sufficient to restore metabolic health. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…These perturbations eventually recover, as hinted by the absence of differential expression after 7 d; however, until baseline is reached, this temporary regulatory background could possibly cause the response to another exposure (repeated SD or other) to differ from that under the pre-SD baseline background. While it is debated whether repeated SD on subsequent days alter the homeostatic response at the phenotypic level in rats (EEG) (53, 54), recent studies in humans found that even 2 nights of recovery sleep were insufficient to completely reverse the metabolic perturbations caused by multiple nights of restricted sleep (55, 56). Follow-up experiments at the molecular level will show how such a transient “new baseline” due to only a partial recovery would influence the response to a second event occurring before full recovery.…”
Section: Resultsmentioning
confidence: 99%
“…These perturbations eventually recover, as hinted by the absence of differential expression after 7 d; however, until baseline is reached, this temporary regulatory background could possibly cause the response to another exposure (repeated SD or other) to differ from that under the pre-SD baseline background. While it is debated whether repeated SD on subsequent days alter the homeostatic response at the phenotypic level in rats (EEG) (53, 54), recent studies in humans found that even 2 nights of recovery sleep were insufficient to completely reverse the metabolic perturbations caused by multiple nights of restricted sleep (55, 56). Follow-up experiments at the molecular level will show how such a transient “new baseline” due to only a partial recovery would influence the response to a second event occurring before full recovery.…”
Section: Resultsmentioning
confidence: 99%
“…These perturbations eventually recover, as hinted by the absence of differential expression after 7 days, however until baseline is reached, this temporary regulatory background could possibly cause the response to another exposure (repeated SD or other) to differ from that under the pre-SD baseline background. While it is debated whether repeated sleep deprivation on subsequent days alter the homeostatic response at the phenotypic level in rats (EEG) (49,50), recent studies in humans found that even two nights of recovery sleep were insufficient to completely reverse the metabolic perturbations caused by multiple nights of restricted sleep (51,52). Follow-up experiments at the molecular level will show how such a transient "new baseline" due to partial recovery would influence the response to a second event occurring before full recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the actigraphy-quantified sleep in a subset of participants from this study (10). Actigraphy-assessed habitual sleep was 8.4 ± 0.1 h/night (mean ± SEM).…”
Section: Actigraphic and Polysomnographic Measures Of Sleep Durationmentioning
confidence: 92%
“…Discrepancies between scorers (if any) >15 min were rectified prior to unblinding; device recordings of activity counts, light levels, and wear/non-wear status were used to aid scoring. Actigraphy scoring methods have previously been described (10,61). A registered polysomnographic technologist staged the in-lab PSG recordings in 30 s windows according to American Academy of Sleep Medicine standards (62,63).…”
Section: Actigraphic and Polysomnographic Sleep Quantitationmentioning
confidence: 99%
See 1 more Smart Citation